Chronopotentiometric Deposition of Nanocobalt Oxide for Electrochromic Auxiliary Active Electrode Application. Issue 19 (5th August 2020) - Pathak, Devesh K.; Chaudhary, Anjali; Tanwar, Manushree; Goutam, Uttam K.; Pfnür, Herbert; Kumar, Rajesh
Abstract : A dense nanofilm of Co3 O4 is synthesized using constant current electrodeposition on a conducting transparent electrode that works not only as a counter electrode but also shows electrochromic (EC) properties on its own. The isolated active nano‐Co3 O4 electrode shows reduction in the redox potential and good color contrast between its yellowish transparent and dark states at different bias conditions. The electrode shows improved color contrast, stability, and cycle life. In situ spectroelectrochemical studies of the nanoelectrode reveals that the bias‐induced redox activity of the metal oxide leads to the color change between yellowish and opaque states. The bias‐induced color change makes it an active EC counter‐ion electrode for appropriate solid‐state EC devices. Abstract : Electrodeposited cobalt oxide nanostructured films show robust electrochromic (EC) properties with applications of small biases, showing switching between transparent yellow and dark brown colors. A nicely packed film with good cycle life makes it a potential candidate for an EC electrode as well as counter electrode in designing a solid‐state EC device.